2017
DOI: 10.1002/andp.201700033
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanoribbons for Electronic Devices

Abstract: Graphene nanoribbons show unique properties and have attracted a lot of attention in the recent past. Intensive theoretical and experimental studies on such nanostructures at both the fundamental and application-oriented levels have been performed. The present paper discusses the suitability of graphene nanoribbons devices for nanoelectronics and focuses on three specific device types -graphene nanoribbon MOSFETs, side-gate transistors, and three terminal junctions. It is shown that, on the one hand, experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 139 publications
(222 reference statements)
1
35
0
1
Order By: Relevance
“…It has been found that for the geometries a/b > 0.02 from Fig. 1a, b, the propagation constant k z (1) is close to the value provided by the parallel-plate waveguide model (8), and no additional iteration steps are required except one.…”
Section: Results Of Simulation and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It has been found that for the geometries a/b > 0.02 from Fig. 1a, b, the propagation constant k z (1) is close to the value provided by the parallel-plate waveguide model (8), and no additional iteration steps are required except one.…”
Section: Results Of Simulation and Discussionsupporting
confidence: 55%
“…These include interconnects, antennas, attenuators, transistors [4,5], and nonlinear devices [6]. Many techniques are used to realize these and other prospective components, such as chemical doping [7], integration of graphene with other materials [3], and graphene nanoribbon or nanodot elements [8]. Some problems of active and passive components are solved by staking the graphene nanosheets or using the quantum-mechanical interaction of graphene layers [9].…”
Section: Introductionmentioning
confidence: 99%
“…石墨烯特殊的结构, 赋予其优 异的物理化学性能, 如杨氏模量将近 1.0 TPa [4][5] , 断裂 强度为 42 N/m [6] , 电子迁移率高达 2×10 5 cm 2 /(V•s) [7] , 热导率可达 5.30×10 3 W/(m•K) [8] . 因此, 石墨烯在复合 材料 [9][10][11][12] 、电子器件 [13][14] 、能量存储 [15][16][17] 、传感器 [18][19][20] 及 生物医药 [21][22][23][24] 等领域有着广泛的应用.…”
Section: 引言unclassified
“…The interfaces between such bubble and substrate (in the case of epitaxial graphene SiC) display unique capacitance effects which lead to the emergence of a mini gap in the electronic band structure of graphene of approximately ⁓5 meV. Therefore, the potential of graphene and graphene containing materials for future applications is immense and already shows promise in fields like nano-electronics [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], nonlinear optics [ 40 ] and plasmonics [ 41 ].…”
Section: Introductionmentioning
confidence: 99%